2021
DOI: 10.2147/ppa.s321175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Holding on Anxiety and Pain During Prostate Biopsies: A Pilot Randomized Controlled Trial

Abstract: Background: Effective pain management is limited for patients during prostate biopsy (PBx). Touch support, such as hand holding, has stress-buffering benefits and effective analgesic effects. We conducted a prospective, single-center randomized clinical trial to assess whether hand holding can reduce patient anxiety, pain, and dissatisfaction during PBx. Methods: Between April 2020 and October 2020, 120 male patients were randomized into three groups: a hand holding with relatives (HR) group, a hand holding wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…No significant differences were found in terms of SFR and the rate of complications (4). The insertion success rate can vary depending on the caliber of UAS, as demonstrated by Li et al (5) They found that the utilization of 10/12 Fr UAS resulted in a higher insertion success rate (91.2% vs. 86.9%, P = 0.006) and lower severity of ureteral wall injury (80.1% vs. 85.2%, P < 0.001) compared to 12/14 Fr UAS. The SFR was similar in both groups.…”
Section: Types Of Uasmentioning
confidence: 96%
“…No significant differences were found in terms of SFR and the rate of complications (4). The insertion success rate can vary depending on the caliber of UAS, as demonstrated by Li et al (5) They found that the utilization of 10/12 Fr UAS resulted in a higher insertion success rate (91.2% vs. 86.9%, P = 0.006) and lower severity of ureteral wall injury (80.1% vs. 85.2%, P < 0.001) compared to 12/14 Fr UAS. The SFR was similar in both groups.…”
Section: Types Of Uasmentioning
confidence: 96%